COLLISIONAL AND POSTCOLLISIONAL TECTONICS OF THE APENNINIC-MAGHREBIAN OROGEN (SOUTHERN ITALY) - Lentini F.; Carbone S.; Guarnieri P. (My University, 2006)
Geological analysis of geophysical data obtained by the interpretation of crustal profiles indicates that in the central Mediterranean region the following structural domains can be distinguished: the foreland domains, an orogenic belt, and the Corsica- Sardinia block. The foreland domains are represented by two continental blocks, the Apulian block to the north and the Pelagian block to the south, belonging respectively to the Adria and to the Africa plates, separated by the oceanic crust of the Ionian Sea. The orogenic belt is located between two oceanic crusts: the old Ionian crust, at the present time subducting beneath the Calabrian arc, and the new crust of the Tyrrhenian Sea. The orogenic belt is represented by a multilayer allochthonous edifice composed of the Calabride chain, which tectonically overlies the so-called Apenninic- Maghrebian chain, which in turn is overthrust onto the upper Miocene and Pliocene top levels of a deep-seated thrust system that originated from the deformation of the innermost carbonates of the Apulian and Pelagian blocks (the external thrust system). The Calabride chain is composed of crystalline nappes originating, since the Eo-Oligocene, from the delaminated margin of the Europe plate. The Apenninic- Maghrebian chain tectonic units derive from the orogenic transport during Oligo- Miocene times of sedimentary sequences deposited in paleogeographic domains located between the Europe and the Afro-Adria plates. These units are composed of meso-Cenozoic shallow-water carbonate successions detached from a continental type of crustal sector named here the Panormide-Apenninic block. This is now recognizable by means of seismic lines shot in the Tyrrhenian off-shore of the southern Apennines and northern Sicily. The meso-Cenozoic basinal units that constitute the Apenninic-Maghrebian chain can be distinguished into two main groups of sequences, originally located on oceanic crusts separated by the Panormide-Apenninic crust: the external ones (Ionides) related to an original basin belonging to part of the Ionian paleo-basin involved in the orogenesis (Lagonegro, Imerese, Sicanian, and Monte Judica units) and the internal ones ascribed to the Alpine Tethys (Liguride-Sicilide units). The previously described allochthonous edifice is characterized by thin-skinned tectonics and represents a roof thrust system resting on the external thrust system, which derived from thick-skinned tectonics that produced folds and reverse faults with relatively moderate horizontal displacements. The external thrust system developed from late Miocene times, contemporaneously with the opening of the Tyrrhenian basin, and is named the Apulian thrust system in southern Italy and the Pelagian- Sicilian thrust belt in Sicily. The crustal sections of the CROP project (Deep Seismic Exploration in the Central Mediterranean and Italy) allow us to distinguish the thickness and distribution of the crusts in this area of the Mediterranean Sea, and they confirm that the foreland continental blocks, the Apulian and the Pelagian blocks, are separated by the Ionian oceanic crust. Both the foreland blocks extend below the orogenic belt, reaching the Tyrrhenian margins, with a gradual thinning and a transition to a Paleo-Ionian slab, probably not active at present time, from which the Ionides detached and overrode the external thrust system. The seismogeological data indicate the presence of a continental block, original basement of the Panormide-Apenninic platforms, that took part in the closure of the sectors of the Paleo-Ionian Sea interposed between the Panormide- Apenninic crust and the Pelagian and Apulian blocks. At the present time, it is colliding with the foreland blocks. Thus, this has been identified as collisional crust. The geologic evidence of this collisional stage is manifested in the northwest-southeastoriented South Tyrrhenian system, which is characterized by dextral faults affecting both off-shore and on-shore areas of Sicily. A mirrorlike sinistral fault system occurs in the southern Apennines. Interpretative seismic reprocessing has permitted clear seismic imaging of the subducted Ionian slab. The distribution of the earthquakes transversally and longitudinally indicates that the slab is narrowing in a vertical direction; thus, at present, the active slab is limited to a short segment between northeastern Sicily (the Vulcano line) and southern Calabria (the Catanzaro line). To the west and to the northeast of these lines, a collisional setting can be recognized. The geological and geophysical data and the volcanological characteristics of the study area permit us to restore the paleogeographic and paleotectonic setting and have allowed us to recognize three orogenic stages: the Eo-Alpine, which originated during Cretaceous-Eocene times but is less evident in the study area; the Balearic stage (late Oligocene-early Miocene), in which the Corsica-Sardinia block collided with the Adria-Africa margins with thrusting of the Alpine Tethydes over Panormide units; and the Tyrrhenian stage (middle Miocene to present), when the onset of the Tyrrhenian back-arc basin occurred and the collisional crust followed the Ionian slab retreat, closing the interposed basin with tectonic transport of the Ionian ocean cover (the Ionides) over the foreland blocks.
Keywords: CALABRIAN ARC; GEODYNAMICS; SICILY; SOUTHERN APENNINES; THRUST TECTONICS; TYRRHENIAN BASIN; Cretaceous; Pliocene; Miocene; Oligocene; Eocene; Mesozoic::Cretaceous; Мезозой::Меловая; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен; Cenozoic::Paleogene::Oligocene; Кайнозой::Палеоген::Олигоцен; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен